Impact of Multimodal Education on Student Competency in Global Transportation - Marudut Bernadtua Simanjuntak (Lembaga Einstein College (LEC), 2024)
This qualitative study explores the influence of multimodal education on student competency within the global transportation industry. Focusing on 39 cadets enrolled in transportation institutions, the research investigates various dimensions including multimodal transportation, logistics, transportation safety, and road management law. Through qualitative research methodologies and descriptive analysis, the study elucidates the nuanced impacts of education on student competency, particularly concerning international and safety standards. The findings highlight the significance of understanding multimodal systems, logistics, transportation safety, and problem-solving skills in preparing students for the complexities of the global transportation sector. The research underscores the importance of integrating multimodal education into transportation curricula and fostering closer collaboration between academia and industry to meet the evolving needs of the transportation industry